Organization and nucleotide sequence analysis of an rRNA and tRNA gene cluster from Caulobacter crescentus. - Feingold, J (1985)
rRNA genes of Caulobacter crescentus CB13 were isolated and shown to be present in two gene clusters in the genome. The organization of each rRNA gene cluster was found to be 5'-16S-tRNA spacer-23S-5S-3'. The DNA sequence of 40% of the 16S rRNA gene, the entire 16S/23S intergenic spacer region, and portions of the 23S rRNA gene were determined. Analysis of the nucleotide sequence in the 16S-23S intergenic spacer region revealed the presence of tRNAIle and tRNAAla genes. Large invert repeat sequences were found surrounding the 16S rRNA gene. These inverted repeat sequences are analogous to the RNase III-processing sites in the E. coli rRNA precursor. Small invert repeat sequences were also found flanking the individual tRNA genes. RNA polymerase-binding studies with restriction fragments of the rRNA gene cluster revealed three regions which bound enzyme, and these regions were shown to contain transcription initiation sites. One of these sites was located within the 16S gene near its 3' end, and the other two were found at the 5' end of the 23S gene.